The effects of augmented feedback on anthropometric, strength and power adaptations. - Weakley, J.; Till, K.; Wilson, K.; Jones, B. (Journal of Australian Strength and Conditioning, 2018)
Augmented feedback during strength and conditioning sessions can augment strength and power adaptations in semi-professional rugby union players. Consequently, practitioners should consider providing immediate kinematic feedback when athletes are resistance training, and sprint time when completing acceleration drills.